Cytotoxicity of cisplatin in bladder cancer is significantly enhanced by application of bcl-2 antisense oligonucleotides - Schaaf, Axel; Sagi, Sreedhar; Langbein, Sigrun; Trojan, Lutz; Alken, Peter; Michel, Maurice Stephan (Urologic oncology, 2004)
Background: The aim of our study was to examine the effects of the combined application of cisplatin and bcl-2 antisense oligonucleotide on human bladder cancer cell lines to determine the possible synergistic effects in cytotoxicity and to estimate its potential value for subsequent in vivo trials. Materials and methods: Human bladder cancer cell lines (UM-UC 3, RT 112, T24/83 and HT 1197) were treated with bcl-2 antisense oligonucleotide, cisplatin, or a combination of both and incubated for 48 h under standard conditions. Cell survival was determined using a Neubauer haemocytometer or standard MTT assay. BCL-2 expression was verified using western blotting. Results: The combined treatment resulted in significant lower cell survival rates compared to individual treatment. Additionally, there was a decrease in cell survival rate with an increase in cisplatin concentration in combined treatment that was not observed in cisplatin mono treatment. Conclusions: For the combined treatment with oligonucleotides and cisplatin a synergistic effect can be strongly suggested. Therefore, further investigations and in vivo trials have to be done to determine the possible benefits for clinical applications.